Dilemmas in health promotion in Brazil: the National Policy under consideration - Martha A. Traverso-Yépez; David Anderson (Faculdade de Medicina de Botucatu (Unesp), 2007)
Despite being a recurrent theme in day-to-day life, health promotion is a complex and multifaceted concept. The purpose of this article is to highlight some of the dilemmas and problematic aspects of institutional ideas about health promotion. It also emphasizes the difficulty of thinking about health promotion, without also considering how to eradicate the deep social iniquities of the Brazilian context. The article develops this line of thinking in depth by analysing the National Health Promotion Policy instituted in 2006, and demonstrates the relevance of deconstructing politically correct discourses and developing processes of reflection in our health-related practices.